How to analyze the impact of bilateral investment treaties on FDI - Andrew Kerner (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2019)
Bilateral investment treaties are often thought to impact the behaviors of multinational corporations, though it is not entirely clear that they do. That ambiguity stems partly from FDI data being ill-suited to answering the question. More suitable data sources exist, however, and should be used.
Keywords: 330